CONVERSATION TEXT ON INDONESIAN LESSONS USING IMAGES IN CLASS V STATE ELEMENTARY SCHOOL 101938 ADOLINA, PERBAUNGAN DISTRICT - Wati, Sari Suka; Sutikno, Sutikno; Kartolo, Rahmat (International Journal of Ethno-Sciences and Education Research, 2022)
Many educators still use conventional teaching materials, namely teaching materials that are ready to use, just buy, instant, without the effort of planning, preparing, and compiling their own and less attracting children's attention in learning. So the image media is used as a development effort in learning Indonesian. This study aims to determine the quality of teaching materials based on the validation of material experts and media experts, to determine the attractiveness of teaching materials based on student responses, and to determine the average increase in student achievement based on pretest and posttest scores. This research was carried out at SDN 101938 Adolina, Perbaungan District, for the 2021-2022 academic year. This research is development research. The subjects of the study were the fifth grade students of SDN 101938 Adolina, Perbaungan District, for the academic year 2021-2022 with a total of 36 students. Data collection techniques used are tests, questionnaires, and documentation. The data analysis technique used is the percentage and the average. The results of the overall quality of teaching materials are good with a percentage of 78%. The results of the attractiveness of teaching materials based on student responses in the limited trial obtained a percentage of 87% with a very interesting category, while in the large group trial a percentage of 85% was obtained with a very attractive category. The average value of the pretest is 6.09, while the average value of the posttest is 8.44, so it can be concluded that there is an increase in the average student achievement.